Fermented Palm Kernel Cake Improves the Rumen Microbiota and Metabolome of Beef Cattle - Wenbo Jiang; Yan Zhang; Haijian Cheng; Xin Hu; Wei You; Enliang Song; Zhiyong Hu; Fugui Jiang (Animals)
In this study, we utilised palm kernel cake as a substrate and fermented it with a composite of bacteria (Pediococcus pentosaceus CGMCC No. 27203 and Lactobacillus plantarum CGMCC No. 27202) and enzymes. We conducted a trial with twenty-four cattle, randomly divided into two groups of twelve cattle each. The control group (CON) was fed the standard farm diet, whereas the treatment group (PKC) received a diet with 3% of soyabean replaced by fermented palm kernel cake. The trial lasted for six weeks. The results showed no significant differences in growth performance between the PKC and CON groups. The abundance of Firmicutes, Bacteroidetes, Proteobacteria, and Spirochaetes was significantly higher in the PKC group than in the CON group. At the genus level, the abundances of Anaeroplasma, norank_f__Bacteroidales_UCG-001, norank_f__Absconditabacteriales_SR1, norank_f__p-251-o5, Prevotellaceae_NK3B31_group, Prevotellaceae_UCG-001, Prevotellaceae_UCG-004, and Treponema significantly increased in the PKC group. Lipid digestion and absorption pathways were significantly enriched in the PKC group. The results indicate that adding fermented palm kernel cake to the diet can increase the abundance of Bacteroidetes and Fibrobacteres in the rumen of beef cattle, enhancing the ability of the PKC group to degrade protein, carbohydrates, and fibrous materials in the feed, thereby improving the feed utilisation efficiency in beef cattle. Adding fermented palm kernel cake to the diet improved carbohydrate metabolism, metabolism of cofactors and vitamins, and nucleotide metabolism. Correlation analysis between the rumen microbiota and metabolic pathways showed that Prevotellaceae_UCG-001 and Prevotellaceae_UCG-003 were positively correlated with amino acid metabolism, Rikenellaceae_RC9_gut_group and Succiniclasticum were positively correlated with metabolism of cofactors and vitamins, and Prevotella and Ruminococcus were positively correlated with nucleotide metabolism. These findings elucidate the differences in rumen microbiota when fermented palm kernel cake is added to the diet, providing a theoretical basis for the application of fermented palm kernel cake in the diet of beef cattle.